Stability of effective rate of rearing in silkworm, Bombyx mori L. due to effect of larval density in the rearing bed (University Journal of Zoology, Rajshahi University, 2007)
Key words: Bombyx mori; larval density; stability Univ. j. zool. Rajshahi Univ. Vol.23, 2004. pp. 37-41